Biosecurity of Poultry Worker Related to Avian Influenza in Bangladesh - Swapan Kumar Roy; Quazi Zahangir Hossain (International Journal of Public Health Science (IJPHS), 2014)
Research on biosecurity of poultry workers of Live Bird Market (LBM) in urban and rural areas related to highly pathogenic avian influenza (AI) was undertaken during March-June, 2014 at Keshabpur upazila (22°48´-22°57´N latitude and 89°06´-89°22´E longitude), Jessore, Bangladesh. A non-randomized (purposive) sampling method was applied and a descriptive type of cross sectional study was performed among 72 workers, dividing them into two groups as 36 urban and 36 rural poultry workers of LBM through split-halves variation technique. They were interviewed confidentially in their work place using a structured pretested questionnaire. Among respondents 53%, 75%, 45%, 81%, and 56% of urban and 50%, 42%, 50%, 89%, and 36% of rural residence had attended up to primary school, knowledge about AI through media like TV and radio, used proper personal protective equipment as mask and gloves, washed their hands and equipment after finishing work and cleaned stalls/cages daily and mostly they used water as a cleaning material, respectively. In urban (14%) and rural (36%) workers used the same vehicle to transport poultry and humans. A combined effort is required to enhance knowledge and change behavior among those most at risk in low-income countries and precautions necessary to avoid spreading the virus among poultry and humans.